Podstawy datowania trzcinieckiego kręgu kulturowego w Polsce środkowej na przykładzie materiałów ze stanowiska w Polesiu w dorzeczu Bzury - Górski, Jacek; Makarowicz, Przemysław; Wawrusiewicz, Adam (Acta Universitatis Lodziensis. Folia Archaeologica, 2011)
The discussion about the periodization of the „Trzciniec” phenomena in Poland arose due to wide-scale rescue excavations which were carried out in recent years. The main source of these analyses is a study on a large series of artifacts from site 1 at Polesie, Łyszkowice commune, Lodz voivodeship, identified on the route of the A2 motorway building (cf. monograph – Górski, Makarowicz, Wawrusiewicz 2011). The site under consideration is situated on Łowicz – Błonie Plain, which is the south-west fragment of the Masovian Plain (fig. 1). It occupies the northern part of a vast plateau (fig. 2) built of eolic sands, spreading between two flows – Zwierzynka on the east, and Ruczaj on the west (right-bank tributaries of the river Bzura). Finds from that period came in the form of settlements and cemeteries and were documented in almost the entire excavated area (fig. 3). The small number of pits (224), their distribution and their poor state of preservation, as well as the erosion of the artifacts (over 61 thousand vessel fragments) suggest a considerable degree of site destruction.